AS MANY LANGUAGES YOU KNOW, SO MANY INDIVIDUALS YOU ARE (interview with V. Moiseev) - N. V. Dolgushina (Рациональная фармакотерапия в кардиологии, 2015)
As many languages you know, so many individuals you are (interview with V. Moiseev).